Investigating Hots on Learning English for Computer for the Fourth Semester English Students at STMIK Pelita Nusantara Medan - Merlin Helentina Napitupulu (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The aim of this research is to investigate Higher Order Thinking Skills of Students’ at STMIK Pelita Nusantara Medan majoring Informatics Engineering on learning English for Computer. The population of this research is the fourth semester English students at STMIK Pelita Nusantara Medan. The total population is 154 students and as the sample was taken with cluster sampling technique. The students were given test which related to HOTS questions. In collecting the data the researcher used instrument to measure the knowledge of the students on learning English for Computer. The test is consists of three types: Analyzing, Evaluating and Creating. The data was analyzed by calculating the students’ score and performed the item analysis to identify the HOTS levels of the students’ score. Based on the analysis, there were found that the students’ ability on learning English for Computer is good level with the most dominant is above 51, consists of 21 students which the percentage in that level is 70 %. The highest score is above 75 consists of 7 students. Therefore the students’ ability in computer is already good. Keywords: HOTS, English for Computers